Sialosignaling: Sialyltransferases as engines of self-fueling loops in cancer progression - Dall'Olio, Fabio; Malagolini, Nadia; Trinchera, Marco; Chiricolo, Mariella (Biochimica et biophysica acta, 2014)
Glycosylation is increasingly recognized as one of the most relevant postranslational modifications. Sialic acids are negatively charged sugars which frequently terminate the carbohydrate chains of glycoproteins and glycolipids. The addition of sialic acids is mediated by sialyltransferases, a family of glycosyltransferases with a crucial role in cancer progression. To describe the phenotypic and clinical implications of altered expression of sialyltransferases and of their cognate sialylated structures in cancer. To propose a unifying model of the role of sialyltransferases and sialylated structures on cancer progression. We first discuss the biosynthesis and the role played by the major cancer-associated sialylated structures, including Thomsen–Friedenreich-associated antigens, sialyl Lewis antigens, α2,6-sialylated lactosamine, polysialic acid and gangliosides. Then, we show that altered sialyltransferase expression in cancer, consequence of genetic and epigenetic alterations, generates a flow of information toward the membrane through the biosynthesis of aberrantly sialylated molecules (inside-out signaling). In turn, the presence of aberrantly sialylated structures on cell membrane receptors generates a flow of information toward the nucleus, which can exacerbate the neoplastic phenotype (outside-in signaling). We provide examples of self-fueling loops generated by these flows of information. Sialyltransferases have a wide impact on the biology of cancer and can be the target of innovative therapies. Our unified view provides a conceptual framework to understand the impact of altered glycosylation in cancer. •A review on the role of sialyltransferases in cancer progression is proposed.•Alteration of sialyltransferases in cancer is a consequence of nuclear changes.•Through sialoglycans, sialyltransferases generate inside-out signaling to membrane.•Membrane sialoglycans can generate outside-in signaling to nucleus.•The existence of sialyltransferase/sialoglycan-fuelled loops is proposed.